The incidence of the host galaxy light in the polarized emission of the blazars 1959+650 and 2201+044 - Sosa, Marina (2014)
We present a study carried out to determine variations in scales ranging from hours to days, both in the total flux and optical linear polarization in two blazars: 1959+650 and 2201+044. Both blazars are relatively nearby active galactic nuclei, so their host galaxies are well resolved, having accurately measured photometric parameters. This allowed us to apply models that take into account the depolarizing effect introduced by the (un-polarized) light of the galaxy, and, at the same time, to evaluate any spurious variation in polarization time-curves due to variable seeing conditions, that affect differently the (pointlike) core and the (extended) host galaxy. Our results provide information on the optical behaviour of high energy blazars, taking advantage of a scarcely explored technique as optical polarimetry with high-temporal resolution.